2018
DOI: 10.1007/s00382-018-4599-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating vector winds in the Asian-Australian monsoon region simulated by 37 CMIP5 models

Abstract: Vector wind plays a crucial role in shaping regional climate through transferring energy and moisture. In this study, we evaluate 37 Coupled Model Intercomparison Project Phase 5 (CMIP5) models and multi-model ensembles (MME) in terms of the climatological mean state, annual cycle, and interannual variability of vector winds in the Asian-Australian monsoon (A-AM) region. Unlike most previous studies those assessed meridional and zonal wind separately, we treat vector wind as a whole by employing a recently dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Agreement of other simulated components of the global monsoon domain with observations is generally strong, and CESM is among the best coupled climate models in reproducing the monsoons (e.g. Huang et al, , Figure ). In this work, various components of the global monsoon are examined including the entirety of the region in Figure , the global monsoon (GM), and its NH (NHM) and SH (SHM) subdomains.…”
Section: Cesm Simulation Of the Global Monsoonmentioning
confidence: 98%
“…Agreement of other simulated components of the global monsoon domain with observations is generally strong, and CESM is among the best coupled climate models in reproducing the monsoons (e.g. Huang et al, , Figure ). In this work, various components of the global monsoon are examined including the entirety of the region in Figure , the global monsoon (GM), and its NH (NHM) and SH (SHM) subdomains.…”
Section: Cesm Simulation Of the Global Monsoonmentioning
confidence: 98%
“…These information are very important for us to understand the model biases. The Taylor diagram can also be generalized as a vector field evaluation (VFE) diagram, which can quantitatively evaluate model performance in simulating vector fields, for example, vector winds (Xu et al, 2016;Huang et al, 2019). A single index or model skill score is certainly necessary to measure model performance but it loses the detail information on model performance.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the overall simulation capability for TC environmental fields, suggested that high-resolution models generally perform better in simulating the wind vector field in the Asian-Australian monsoon region (Huang et al, 2019). Of course, the above relationship is not always valid.…”
Section: Evaluation Of the Performance Of Cmip6 Models In Five Ocean Regionsmentioning
confidence: 99%